2017
DOI: 10.1080/09537287.2017.1324184
|View full text |Cite
|
Sign up to set email alerts
|

Barriers in Green Lean implementation: a combined systematic literature review and interpretive structural modelling approach

Abstract: Green Lean has recently emerged as an alternative strategy for organizations to pursue both operational and sustainability excellence. The interest on this approach has rapidly risen in both academic and industry circles. However, despite this interest, very limited research has focused on its implementation, and no research has investigated the barriers that hinder the success of such activity. This study investigates the Green Lean implementation barriers and their contextual relationships and effects on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
108
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(121 citation statements)
references
References 85 publications
(56 reference statements)
6
108
0
1
Order By: Relevance
“…On the other hand, another set of practices that have contributed to sustainability are those of Lean Manufacturing (LM) (Garza-Reyes, 2015a). In this line, recent studies have demonstrated that LM can be a significant contributor to address current sustainability issues (Cherrafi et al, 2017a;Nadeem et al, 2017;Cherrafi et al, 2016;Garza-Reyes et al, 2016;Chiarini, 2014;Jabbour et al, 2013). Consequently, Lean and Green initiatives have been merged to deploy operational strategies that aim at not only helping organizations to achieve their economic objectives but also improve their sustainability performance (Garza-Reyes, 2015b).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, another set of practices that have contributed to sustainability are those of Lean Manufacturing (LM) (Garza-Reyes, 2015a). In this line, recent studies have demonstrated that LM can be a significant contributor to address current sustainability issues (Cherrafi et al, 2017a;Nadeem et al, 2017;Cherrafi et al, 2016;Garza-Reyes et al, 2016;Chiarini, 2014;Jabbour et al, 2013). Consequently, Lean and Green initiatives have been merged to deploy operational strategies that aim at not only helping organizations to achieve their economic objectives but also improve their sustainability performance (Garza-Reyes, 2015b).…”
Section: Introductionmentioning
confidence: 99%
“…Green Lean, has recently taken relevance in the scholarly literature (e.g. Verrier et al, 2016;Cherrafi et al, 2017a;Cherrafi et al, 2016;Garza-Reyes, 2015a; Garza-Reyes, 2015b) due to the synergetic characteristics of Lean and Green and the positive results associated to their integration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many applications of the ISM have been identified by a variety of researchers in various areas, such as identifying the critical success factors for safety management, the factors influencing e-diplomacy implementation, assessing contributory factors in potential systemic accidents, and analyzing the influencing factors of food safety [25][26][27][28][29][30][31][32][33][34][35][36]. The ISM is also applied in the supply chain, but there are few applications in logistics [37,38].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lean can be considered as "a way"; "a process"; "a set of principles"; "a set of tools and techniques"; "an approach"; "a concept"; "a philosophy"; "a practice"; "a system"; "a program"; "a manufacturing paradigm"; or "a model". Lean can be considered as a strategy (Cherrafi et al, 2017) or methodology (Laureani & Antony, 2017;Tasdemir & Gazo, 2018). Tiamaz and Souissi (2017) have analyzed the Lean models and concluded that these Lean models interpret the Lean in different ways.…”
Section: Lean Understanding In the Literaturementioning
confidence: 99%